2000
DOI: 10.1034/j.1600-0536.2000.043003150.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis from glutaraldehyde in health‐care workers

Abstract: Glutaraldehyde is considered the disinfectant of choice for sterilizing medical and dental equipment. Unfortunately, glutaraldehyde has many toxic side-effects, including the ability to induce allergic contact dermatitis. In a 5-year study at the University of Kansas, 468 patients were patch tested to glutaraldehyde. A comparison of results was made between those employed in a healthcare related field and those who were not. Health-care workers (HCWs) were more than 8x more likely to be allergic to glutaraldeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 15 publications
2
77
1
2
Order By: Relevance
“…Allergic contact dermatitis is caused by working materials (gloves, metals, epoxy and acrylic resins) and other chemicals; for example, disinfecting agents for hygiene such as glutharaldeides 35 and drugs, that may also be irritants. Urticaria caused by latex in gloves is not rare 20 and additives used in the vulcanization process of rubber gloves (dialkyl thioureas) have been considered the most common sensitizing agents for health professionals 36 .…”
Section: Occupational Dermatitis In Health Professionalsmentioning
confidence: 99%
“…Allergic contact dermatitis is caused by working materials (gloves, metals, epoxy and acrylic resins) and other chemicals; for example, disinfecting agents for hygiene such as glutharaldeides 35 and drugs, that may also be irritants. Urticaria caused by latex in gloves is not rare 20 and additives used in the vulcanization process of rubber gloves (dialkyl thioureas) have been considered the most common sensitizing agents for health professionals 36 .…”
Section: Occupational Dermatitis In Health Professionalsmentioning
confidence: 99%
“…Patch-testing has shown that GA is also capable of inducing allergic contact dermatitis (39)(40)(41). Allergic contact dermatitis caused by workplace substances has important occupational repercussions, as it may lead to persistent dermatitis, which then requires a change of career (38). Nethercott et al for example, found that five of their patients with GA-related contact dermatitis were forced to change their occupation because of the disease (39).…”
Section: Occupational Disorders From Glutaraldehydementioning
confidence: 99%
“…The substance is a well-known sensitizer, with chronic exposure leading to sensitization in certain people who regularly come into contact with GA at work. In one study, health care workers were more than eight times as likely to be allergic to GA, than people who were not employed in health care (38). Patch-testing has shown that GA is also capable of inducing allergic contact dermatitis (39)(40)(41).…”
Section: Occupational Disorders From Glutaraldehydementioning
confidence: 99%
See 2 more Smart Citations